Physical and biological treatment technologies of slaughterhouse wastewater: a review - Musa, Mohammed Ali; Idrus, Syazwani (MDPI AG, 2021)
Physical and biological treatment technology are considered a highly feasible and economic way to treat slaughterhouse wastewater. To achieve the desired effluent quality for disposal or reuse, various technological options were reviewed. However, most practical operations are accompanied by several advantages and disadvantages. Nevertheless, due to the presence of biodegradable organic matter in slaughterhouse waste, anaerobic digestion technology is commonly applied for economic gain. In this paper, the common technologies used for slaughterhouse wastewater treatment and their suitability were reviewed. The advantages and disadvantages of the different processes were evaluated. Physical treatments (dissolved air floatation (DAF), coagulation–flocculation and sedimentation, electrocoagulation process and membrane technology) were found to be more effective but required a large space to operate and intensive capital investment. However, some biological treatments such as anaerobic, facultative lagoons, activated sludge process and trickling filters were also effective but required longer start-up periods. This review further explores the various strategies being used in the treatment of other wastewater for the production of valuable by-products through anaerobic digestion.